What makes an excellent reader? Short-term memory contrasts between two groups of children - Kemény, Ferenc; Aranyi, Gabor; Pachner, Orsolya; P. Remete, Eszter; Laskay-Horváth, Claudia (Frontiers in Education, 2024)
Purpose Research on the association of short-term memory (STM) and reading expertise are dominated by studies with typically developing children and children with reading impairment. Many studies confirmed the role of short-term memory in reading development and reading, especially in the case of verbal and phonological STM. The current study takes an unusual perspective by contrasting age-appropriate readers with excellent readers (reading performance with at least 1 SD above average) on three different short-term memory skills: phonological STM, verbal STM and visuospatial STM. Methods We identified and recruited six groups of children. Three groups performed at least one SD above average in two standardized reading tasks (excellent readers), the three control groups performed within the domain of ±0.5 SD on reading (age-appropriate readers). One group of excellent readers and one group of age-appropriate readers participated in a Phonological Short-Term Memory (STM) task, one pair of groups participated in a Verbal STM task, whereas the last pair participated in a Visuospatial STM task. Results Pairwise comparisons demonstrated that excellent readers outperformed age-appropriate readers in Visuospatial STM. Phonological STM only differed across the groups after controlling for age. No group difference was observed in Verbal STM. Conclusion Our results confirm the role of short-term memory in reading expertise. However, data highlights that visuospatial and phonological information becomes more relevant in above-average readers. Results are discussed along grain-size theory, and whether and how focused educational programs can build on visuospatial short-term memory training to achieve better reading.